An Illustrated Guide to Dinosaur Feeding Biology - Nabavizadeh, Ali, 1987-; Weishampel, David B., 1952- (Book collections on Project MUSE., 2023)
"This beautifully illustrated exploration of the diversity, anatomy, and evolution of dinosaur feeding adaptations is the first and only in-depth look at this crucial aspect of paleoecology.In An Illustrated Guide to Dinosaur Feeding Biology, experts Ali Nabavizadeh and David B. Weishampel bring dinosaurs to life on the page by exploring and illustrating their feeding adaptations. Whether dinosaurs were carnivorous, herbivorous, or omnivorous, their evolution produced a multitude of specialized adaptations that helped shape their ecologies. Dinosaur skulls show a variety of bone and joint specializations ideal for withstanding stresses and strains induced by high bite forces with strong jaw musculature. The bladed, steak-knife dentition of many carnivorous dinosaurs was well-suited for slicing meat and crushing bones, while the leaf-shaped, sometimes tightly packed dentition of many herbivorous dinosaurs was ideal for grinding up a variety of plant material.The first book of its kind, An Illustrated Guide to Dinosaur Feeding Biology is a synthesis of over a century of dinosaur feeding biology research, from the earliest hypotheses in the 1800s to today's studies using advanced techniques. Intended for both researchers and dinosaur enthusiasts alike, this book discusses functional morphological studies highlighting comparative anatomy, tooth wear, muscle reconstruction, and biomechanical analysis using modeling techniques like finite element analysis and multibody dynamics analysis. In addition to the feeding apparatus, Nabavizadeh and Weishampel explore postcranial adaptations and discuss the evolution of dinosaurs and their paleoecology more broadly. Integrating these various factors improves our understanding of dinosaurs as the living beings they were in their ecosystems millions of years ago and ultimately expands our knowledge and perspective of today's ecosystems by framing them in a broader evolutionary context"--